Sniffer dogs as an emerging approach for water leakage detection - Zhong, Jiazhi; Chen, Dongdong (Water science & technology. Water supply, 2023)
Effective control of water leakage is a critical aspect for ensuring the high-quality development of the water sector. In recent years, the utilization of sniffer dogs in water leakage detection has emerged as a promising technology, progressing from laboratory experiments to small-scale real-world applications. Leveraging their remarkable ability to trace chlorine, sniffer dogs have demonstrated an impressive accuracy and high efficiency in detecting underground pipe leaks. This mini-review comprehensively examines the advancements in sniffer dog usage for leak detection, provides an overview of various application methods, and elucidates the conditions and limitations associated with each approach. It also delves into the management mechanisms of sniffer dogs, offering a comparative analysis of different management models. Lastly, this review addresses the challenges inherent in applying sniffer dogs to water leak detection, poses pertinent research questions concerning sniffer dogs' training and the expansion of odour fingerprint, and presents a forward-looking perspective on the subject.